(untitled) (Journal of Hama University, 2020)
This research aims to study a number of indicators of the financial performance of traditional private commercial banks operating in Syria to identify whether these banks still has good liquidity and solvency according to international standards. It also aims to identify its profitability, and then to know how to rely on it to finance public and private projects with loans and credit facilities in the reconstruction phase whith was destroyed by the war. To achieve this goal, data was collected from the financial statements of the traditional private commercial banks operating in Syria during the period from 2009 to 2017. Then a number of financial ratios were extracted such as Cash Ratio and the employment ratio, the financial solvency ratio, the rate of return on Assets and the rate of return on equity. And then compare these ratios with reference ratios to judge the soundness of the financial position of the studied banks. The results of the study showed that the studied banks have good solvency, with the mathematical average of the solvency ratio reaching 20%. As for the profitability of the studied banks, it was found that they are very low, as the results showed a low rate of return on assets and rate of return on property rights. The average of these rates, respectively, was 2.4%, 9.4%. As for liquidity ratios, the results showed that banks maintained high levels of liquidity during the crisis period.